Development of a multigenerational digital lifestyle intervention for women cancer survivors and their families. Issue 1 (4th December 2019) - St. George, Sara M.; Noriega Esquives, Blanca; Agosto, Yaray; Kobayashi, Marissa; Leite, Rafael; Vanegas, Dario; Perez, Alejandra T.; Calfa, Carmen; Schlumbrecht, Matthew; Slingerland, Joyce; Penedo, Frank J.
Abstract: Objectives: This paper presents the results of a study developed to inform the design of a multigenerational digital lifestyle intervention for overweight/obese women cancer survivors and their families. We followed the first six phases of the Integrate, Design, Assess, and Share (IDEAS) framework. Methods: Grandmothers with breast, endometrial, or ovarian cancers (n = 46; 66.1 ± 0.9 years old; 34% Hispanic, 33% non‐Hispanic black, 33% non‐Hispanic white) self‐reported their lifestyle behaviors, family structure, mobile device use, and interest in a family‐based lifestyle intervention. A randomly selected subset of 21 participants subsequently completed qualitative interviews to understand their family relationships, weight‐related challenges, and feedback on intervention prototypes. Results: Participants reported low fruit intake (0.9 ± 0.1 servings/day), moderate vegetable intake (3.0 ± 0.2 servings/day), and high levels of moderate physical activity (990 ± 234 MET‐minutes/week). The majority owned a smartphone (93%) and expressed interest in family‐based programs (80%) that focused on weight management (91%). Qualitative data were collapsed into seven intervention considerations, including: capitalizing on existing familial support, involving local family who need lifestyle change, tapping into survivors' internal strengths, validating prior weight loss, overcoming barriers to sustained lifestyle change, providing information on cancer risk, and motivating families through reinforcing activities. Conclusions: Following the IDEAS framework, our next steps are to develop a fully‐functioning prototype and conduct a randomized pilot trial to test the feasibility and effects of a digital intervention that empowers racially/ethnically diverse overweight/obese women cancer survivors to improve their physical activity and dietary intake and to lose weight by encouraging healthy lifestyle behaviors in their children and grandchildren.